2006
DOI: 10.1186/1475-2891-5-29
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Thanksgiving Holiday on weight gain

Abstract: Background: More people than ever are considered obese and the resulting health problems are evident. These facts highlight the need for identification of critical time periods for weight gain. Therefore the purpose was to assess potential changes that occur in body weight during the Thanksgiving holiday break in college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 24 publications
3
52
3
Order By: Relevance
“…They also found that BMI was associated with weight gain, with overweight/obese participants gaining more weight than participants in the normal BMI category 45 . Twenty-nine papers were located that reported weight change in non-clinical nonpregnant female populations in the age range of 18-36 years, of which 27 studies reported weight gain.…”
Section: Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…They also found that BMI was associated with weight gain, with overweight/obese participants gaining more weight than participants in the normal BMI category 45 . Twenty-nine papers were located that reported weight change in non-clinical nonpregnant female populations in the age range of 18-36 years, of which 27 studies reported weight gain.…”
Section: Activitymentioning
confidence: 97%
“…This may be a particular problem during the holiday season when cultural and social influences combine to create a high risk environment for weight gain 45,[48][49][50] . However, few of the University studies considered changes in other behavioural factors that were addressed in the 'single' determinant papers, such as smoking and contraceptive use.…”
Section: Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon of drastic change is mainly observed during the summer, winter, and thanksgiving holidays, among others [6][7][8]. Educational institutions, then, have a great responsibility in promoting healthy lifestyle habits, considering children spend most of the day in school rather than home [6].…”
Section: Introductionmentioning
confidence: 99%
“…These indicators can remain elevated for several months and even years, increasing the likelihood of being overweight or obese in adulthood [7,9].…”
Section: Introductionmentioning
confidence: 99%